The effects of gonadal tissue/gamete cryopreservation on microRNAs - Islam, Nadia (2020)
Advanced technologies have steadily been established for conserving the potential of biological parenthood in couples who are at risk of losing their fertility due to suffering from benign, malignant cancers as well as other genetic diseases. Methods for fertility preservation differ significantly, depending mainly on the patient’s age and the disease they are suffering from. Cryopreservation of gametes has been suggested to be a putative novel approach to preserving fertility in women and men who are at risk of losing fertility. However, the effects of the freezing/thawing process are not fully understood and ways to assess the tissue’s potential to perform normally after thawing, are an important research goal.